KONDISI SOSIAL DAN KEBIASAAN PETANI PADI MENGGUNAKAN INPUT PRODUKSI PADI (Oryza sativa, L.) DI KABUPATEN INDRAMAYU - Wiwik Ambarsari (Gema Wiralodra, 2019)
This study aims to determine the social conditions and habits of rice farmers in the use of input production of lowland rice farming in Indramayu Regency. The research location is in 3 Districts of Indramayu Regency, namely Sliyeg, Lelea, and Gabuswetan Districts. This research was conducted with a survey approach, descriptive quantitative and qualitative. Sampling of rice farmers was carried out by multistage purposive sampling totaling 120 people. The results of this study are the social conditions of the farmers, 70% of the productive age, 60% are uneducated, 65% are very experienced, and 60% of the land area is under 1 hectare. The habit of using production inputs, 85% already use certified and superior varieties of rice seeds, 71% use inorganic fertilizers, and 93% use inorganic pesticides.